International Collaborative Governance in Preventing Irregular Indonesian Migrant Workers to Malaysia - Warsono, Hardi; Hanura, Marten; Hanani, Retna (JURNAL ILMU SOSIAL, 2022)
The issue of migrant workers is of immediate and urgent interest in the world today. The complexity of migrant worker issues makes this subject a conceptual and analytical appeal that continues to require new studies, including the complex issue of Indonesian Migrant Workers (PMI) to Sabah. The issue of migrant workers cannot be handled individually, considering its transnational nature. Therefore, cooperation and collaboration with various related institutions are required. This article aims to determine the collaboration of various institutions in preventing and reducing the problem of Irregular Indonesian Migrant Workers (PMI) to Sabah. This study used a qualitative descriptive method. Data was collected through in-depth interviews with purposive sampling techniques, direct observation, and literature review. Issues were analyzed using the concept of International Collaborative Governance. The findings reveal that there are efforts made by various parties to cooperate and collaborate in preventing and reducing the presence of Irregular Indonesian Migrant Workers. However, the results were not optimal because the leading institution was not strong enough to coordinate all the parties involved.